Performance ratios for managerial decision‐making in a growing firm - Ponikvar, Nina; Tajnikar, Maks; Pušnik, Ksenja (Journal of Business Economics and Management, 2009)
This paper investigates the impact of firms’ growth rate on various financial and non‐financial performance ratios. The study tests the hypothesis that variations in growth rates across firms relate to differences in the values of ratios of profitability, liquidity, current assets, and solvency, as well as the break‐even point, revenue per employee, average costs, labour costs, capital costs, capacity utilization, productivity and efficiency. In order to estimate the impact of growth on financial and non‐financial indicators while also accounting for unobservable individual effects of each firm, the study assesses several two‐way fixed effect panel models with regression analysis. Authors show that knowing the impact of growth rates on financial and non‐financial ratios gives managers of growing firms additional relevant information for making business decisions.First Publish Online: 09 Jun 2011